Update on motherisk updates. Seven years of questions and answers. - Einarson, Adrienne (2002)
QUESTION: Every month I read the Motherisk Updates in your journal and find them very helpful in counseling my patients on exposures during pregnancy and breastfeeding. I was wondering: what are the most common questions you receive from family physicians? ANSWER: Since the Motherisk Update began, we have received an increasing number of inquiries from family physicians across Canada. Most questions are about drug exposures. The three classes of drugs asked about most often are antidepressants, antiepileptics, and antihistamines.